In vivo and in vitro models of hepatocellular carcinoma: Current strategies for translational modeling - Romualdo, Guilherme Ribeiro [UNESP]; Leroy, Kaat; Costa, Cícero Júlio Silva; Prata, Gabriel Bacil [UNESP]; Vanderborght, Bart; da Silva, Tereza Cristina; Barbisan, Luís Fernando [UNESP]; Andraus, Wellington; Devisscher, Lindsey; Câmara, Niels Olsen Saraiva; Vinken, Mathieu; Cogliati, Bruno (MDPI, 2021)
Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide and the third leading cause of cancer‐related death globally. HCC is a complex multistep disease and usually emerges in the setting of chronic liver diseases. The molecular pathogenesis of HCC varies according to the etiology, mainly caused by chronic hepatitis B and C virus infections, chronic alcohol consumption, aflatoxin‐contaminated food, and non‐alcoholic fatty liver disease associated with metabolic syndrome or diabetes mellitus. The establishment of HCC models has become essential for both basic and translational research to improve our understanding of the pathophysiology and unravel new molecular drivers of this disease. The ideal model should recapitulate key events observed during hepatocarcinogenesis and HCC progression in view of establishing effective diagnostic and therapeutic strategies to be translated into clinical practice. Despite considerable efforts currently devoted to liver cancer research, only a few anti‐HCC drugs are available, and patient prognosis and survival are still poor. The present paper provides a state-of‐the‐art overview of in vivo and in vitro models used for translational modeling of HCC with a specific focus on their key molecular hallmarks.
Keywords: Animal model; Cell culture; Epigenetic alteration; Gene mutation; Hepatocarcinogenesis; Liver cancer; Translational research